Acetate Promotes a Differential Energy Metabolic Response in Human HCT 116 and COLO 205 Colon Cancer Cells Impacting Cancer Cell Growth and Invasiveness - Rodríguez-Enríquez, Sara; Robledo-Cadena, Diana Xochiquetzal; Gallardo-Pérez, Juan Carlos; Pacheco-Velázquez, Silvia Cecilia; Vázquez, Citlali; Saavedra, Emma; Vargas-Navarro, Jorge Luis; Blanco-Carpintero, Betsy Alejandra; Marín-Hernández, Álvaro; Jasso-Chávez, Ricardo; Encalada, Rusely; Ruiz-Godoy, Luz; et al. (Frontiers in Oncology, 2021)
Under dysbiosis, a gut metabolic disorder, short-chain carboxylic acids (SCCAs) are secreted to the lumen affecting colorectal cancer (CRC) development. Butyrate and propionate act as CRC growth inhibitors but they might also serve as carbon source. In turn, the roles of acetate as metabolic fuel and protein acetylation promoter have not been clearly elucidated. To assess whether acetate favors CRC growth through active mitochondrial catabolism, a systematic study evaluating acetate thiokinase (AcK), energy metabolism, cell proliferation and invasiveness was performed in two CRC cell lines incubated with physiological SCCAs concentrations. In COLO205, acetate (+glucose) increased the cell density (50%), mitochondrial protein content (3-10 times), 2-OGDH acetylation and oxidative phosphorylation (OxPhos) flux (36%), whereas glycolysis remained unchanged vs. glucose-cultured cells; the acetate-induced OxPhos activation correlated with a high AcK activity, content and acetylation (1.5-6 fold). In contrast, acetate showed no effect on HCT116 cell growth, OxPhos, AcK activity, protein content and acetylation. However, a substantial increment in the HIF-1α content, HIF-1α-glycolytic protein targets (1-2.3 times) and glycolytic flux (64%) was observed. Butyrate and propionate decreased the growth of both CRC cells by impairing OxPhos flux through mitophagy and mitochondrial fragmentation activation. It is described, for the first time, the role of acetate as metabolic fuel for ATP supply in CRC COLO205 cells to sustain proliferation, aside from its well-known role as protein epigenetic regulator. The level of AcK determined in COLO205 cells was similar to that found in human CRC biopsies showing its potential role as metabolic marker.